Gugatan Perbuatan Melawan Hukum Dalam Jual Beli Tiket Konser Coldplay - Nauva Amanda; Nawal Essam Yahia; Callista Anastasia Shallom Poerba; Cheryl Gladisya Kafka; Katrina Anggi Hasian Kaban; Dwi Aryanti Ramadhani (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the case of a lawsuit for unlawful acts in buying and selling Coldplay concert tickets in Jakarta. The main focus is on the fraud case committed by Ghisca Debora Aritonang (GDA), who sold fake tickets to consumers. This case is included in the category of default and unlawful acts, with material and non-material losses suffered by the victims. Based on Articles 1365 and 1366 of the Civil Code (KUHPer), victims can claim compensation. This study also discusses the elements of unlawful acts, including unlawful acts, the existence of losses, causal relationships between actions and losses, and the fault or negligence of the perpetrators. The study highlights the importance of tighter scrutiny by concert organisers and increased consumer awareness of buying tickets online to prevent similar incidents in the future.